PENGARUH KUALITAS PRODUK, HARGA DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN HANDPHONE BLACKBERRY (Studi Pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro Semarang) - Suci Widyawati; Naili Farida; Andi Wijayanto (Universitas Diponegoro, 2013)
BlackBerry smartphone is one of the leading products in Indonesia. BlackBerry has a high market share compared with other brands of smartphone, but BlackBerry users consumer satisfaction index has declined. It is very influential on consumer loyalty to BlackBerry mobile phone. This study aimed to determine the effect of product quality, price and customer value on customer satisfaction BlackBerry mobile phone. Population in this research is a BlackBerry mobile phone users in FISIP UNDIP Semarang. Samples were taken 100 respondents and the sampling technique used was purposive sampling technique, and then using accidental sampling technique. Measurement scale using a Likert scale. Data analysis using simple linear regression and multiple regression test with SPSS 18.0. Based on the survey results revealed that the quality of the product, price, and customer value and significant positive impact on customer satisfaction, either partially or simultaneously. Variable “product quality” affects “customer satisfaction” that is equal to 46.6%.Variables “customer satisfaction” affect prices by 27,1%. Variables “customer value” affect “customer satisfaction” that is equal to 51,0%. Simultaneously, the variable product quality, price, and customer value affects customer satisfaction at 72.2%. It means that the better the quality of the product, the price according to customer desires, and high customer value, it can improve customer satisfaction.